Prediagnostic alterations in circulating bile acid profiles in the development of hepatocellular carcinoma. Issue 8 (11th January 2022) - Stepien, Magdalena; Lopez‐Nogueroles, Marina; Lahoz, Agustin; Kühn, Tilman; Perlemuter, Gabriel; Voican, Cosmin; Ciocan, Dragos; Boutron‐Ruault, Marie‐Christine; Jansen, Eugene; Viallon, Vivian; Leitzmann, Michael; Tjønneland, Anne; et al.
Abstract: Bile acids (BAs) play different roles in cancer development. Some are carcinogenic and BA signaling is also involved in various metabolic, inflammatory and immune‐related processes. The liver is the primary site of BA synthesis. Liver dysfunction and microbiome compositional changes, such as during hepatocellular carcinoma (HCC) development, may modulate BA metabolism increasing concentration of carcinogenic BAs. Observations from prospective cohorts are sparse. We conducted a study (233 HCC case‐control pairs) nested within a large observational prospective cohort with blood samples taken at recruitment when healthy with follow‐up over time for later cancer development. A targeted metabolomics method was used to quantify 17 BAs (primary/secondary/tertiary; conjugated/unconjugated) in prediagnostic plasma. Odd ratios (OR) for HCC risk associations were calculated by multivariable conditional logistic regression models. Positive HCC risk associations were observed for the molar sum of all BAs (ORdoubling = 2.30, 95% confidence intervals [CI]: 1.76‐3.00), and choline‐ and taurine‐conjugated BAs. Relative concentrations of BAs showed positive HCC risk associations for glycoholic acid and most taurine‐conjugated BAs. We observe an association between increased HCC risk and higher levels of major circulating BAs, from several years prior to tumor diagnosis and after multivariable adjustment for confounders and liver functionality. Increase in BA concentration is accompanied by a shift in BA profile toward higher proportions of taurine‐conjugated BAs, indicating early alterations of BA metabolism with HCC development. Future studies are needed to assess BA profiles for improved stratification of patients at high HCC risk and to determine whether supplementation with certain BAs may ameliorate liver dysfunction. Abstract : What's new? Bile acids, which are synthesized and metabolized in the liver, perform essential metabolic, regulatory and signaling functions, but can also promote cell proliferation, inflammation and oxidative stress. Here, the authors tested whether bile acid metabolism correlated with hepatocellular carcinoma (HCC). They compared 233 case‐control pairs and quantified 17 different bile acids from plasma samples taken prior to diagnosis. They found that changes in bile acid metabolism predate the onset of cancer by several years. People who went on to develop HCC had an overall increase in circulating bile acids, plus an increase in the proportion of taurine‐conjugated bile acids.